Konstrukcja art. 157 § 4 i § 5 k.k. a ochrona pokrzywdzonych będących osobami najbliższymi - Łątka, Monika; Strassberger, Karol (Czasopismo Prawa Karnego i Nauk Penalnych, 2020)
Before the amendment in 2010, regulation of Article 157 of the Polish Criminal Code was clearer, and thus gave the injured party a better chance to react appropriately in the event of being injured by this type of prohibited act. Currently, § 4 of this Article prefers the protection of the immediate family members who live together with a perpetrator. However, this regulation does not pay the same attention to other persons who could also live together with such perpetrators. Moreover, it is more “profitable” for a perpetrator to pour boiling water on his sister than to scratch her hand with a fingernail, because the defective regulation has led to a distortion of the amendment’s aim which was to prevent domestic violence. Furthermore, the regulation does not comply with the definition of domestic violence and it does not regulate the problem in more reprehensible cases, while with minor injuries it interferes before domestic violence even takes place.